2013
DOI: 10.1016/j.econmod.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Variables and South African Stock Return Predictability

Abstract: We examine both in-sample and out-of-sample predictability of South African stock return using macroeconomic variables. We base our analysis on a predictive regression framework, using monthly data covering the in-sample period between 1990:01 and 1996:12, and the out-of sample period commencing from 1997:01 to 2010:06. For the insample test, we use the t-statistic corresponding to the slope coefficient of the predictive regression model, and for the out-of-sample tests we employ the MSE-F and the ENC-NEW test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 46 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…From the result of exchange rate volatility estimates, the coefficients of the magnitude of the volatility (β) and that of the alpha (α) are significant at 1% level of significant, an indication that large shocks in the exchange rate increase volatility in the share price. This is supported by earlier works like Chinzara (2011), Gupta and Modise (2011) for South African economy, Abdalla and Murinde (1997) for India, Korea and Pakistan but contradicts Ibrahim and Aziz (2003) results on the Malaysian economy, Ozair (2006) for the US, Takeshi (2008) for the Indian economy. Similarly, the result from the oil price volatility estimates shows that both the magnitude (β) and that of the α are high, positive and significant at 1% level of significance, this implies that large innovation in the oil price will provoke volatility in the stock market to increase.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…From the result of exchange rate volatility estimates, the coefficients of the magnitude of the volatility (β) and that of the alpha (α) are significant at 1% level of significant, an indication that large shocks in the exchange rate increase volatility in the share price. This is supported by earlier works like Chinzara (2011), Gupta and Modise (2011) for South African economy, Abdalla and Murinde (1997) for India, Korea and Pakistan but contradicts Ibrahim and Aziz (2003) results on the Malaysian economy, Ozair (2006) for the US, Takeshi (2008) for the Indian economy. Similarly, the result from the oil price volatility estimates shows that both the magnitude (β) and that of the α are high, positive and significant at 1% level of significance, this implies that large innovation in the oil price will provoke volatility in the stock market to increase.…”
Section: Discussionsupporting
confidence: 56%
“…Hsing (2011) observed that negative, inconsequential relationships exist between nominal effective exchange rate and South Africa stock market index. Gupta and Modise (2011) observed that a positive relationship exist between stock price and world oil price for the South Africa economies. For the Chinese economy, Rong-Gang Cong et al (2008) examined the interactive relationship between oil price volatility and the Chinese stock market from the period 1996-2007 using VAR estimation techniques and observed that oil price volatility have no significant impact on stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…In empirical studies these have been identified as important drivers of equity prices (Chen et al 1986;Rapach et al 2005. For South Africa, Gupta andModise (2013) find that interest rates, money supply, and growth of world oil production affect stock prices.…”
Section: Pricesmentioning
confidence: 99%
“…But it should be noted that although Islamic finance is not immune to the global financial crisis, there is evidence that it has performed better than its conventional counterparts. Syed When the currency depreciates in value, the increasing price of import commodities in raw materials may cause industrialists and the business owners to be seriously affected [10,21]. This in turn affects the banks' risk-sharing profits.…”
Section: Lessons From the Global Financial Crises (Gfc)mentioning
confidence: 99%